The role of gut microbiome and its interaction with arsenic exposure in carotid intima-media thickness in a Bangladesh population. (February 2019) - Wu, Fen; Yang, Liying; Islam, Muhammad Tariqul; Jasmine, Farzana; Kibriya, Muhammad G.; Nahar, Jebun; Barmon, Bhaswati; Parvez, Faruque; Sarwar, Golam; Ahmed, Alauddin; Eunus, Mahbub; Islam, Tariqul; et al.
Abstract: Background: Emerging data suggest that inorganic arsenic exposure and gut microbiome are associated with the risk of cardiovascular disease. The gut microbiome may modify disease risk associated with arsenic exposure. Our aim was to examine the inter-relationships between arsenic exposure, the gut microbiome, and carotid intima-media thickness (IMT)—a surrogate marker for atherosclerosis. Methods: We recruited 250 participants from the Health Effects of Arsenic Longitudinal Study in Bangladesh, measured IMT and collected fecal samples in year 2015–2016. 16S rRNA gene sequencing was conducted on microbial DNA extracted from the fecal samples. Arsenic exposure was measured using data on arsenic concentration in drinking water wells over time to derive a time-weighted water arsenic index. Multivariable linear regression models were used to test the inter-relationships between arsenic exposure, relative abundance of selected bacterial taxa from phylum to genus levels, and IMT. Results: We identified nominally significant associations between arsenic exposure, measured using either time-weighted water arsenic or urinary arsenic, and the relative abundances of several bacterial taxa from the phylum Tenericutes, Proteobacteria, and Firmicutes . However, none of the associations retained significance after correction for multiple testing. The relative abundances of the family Aeromonadaceae and genus Citrobacter were significantly associated with IMT after correction for multiple testing ( P -value = 0.02 and 0.03, respectively). Every 1% increase in the relative abundance of Aeromonadaceae and Citrobacter was related to an 18.2-μm (95% CI: 7.8, 28.5) and 97.3-μm (95% CI: 42.3, 152.3) difference in IMT, respectively. These two taxa were also the only selected family and genus using the LASSO variable selection method. There was a significant interaction between Citrobacter and time-weighted water arsenic in IMT ( P for interaction = 0.04). Conclusions: Our findings suggest a role of Citrobacter in the development of atherosclerosis, especially among individuals with higher levels of arsenic exposure. Highlights: We identified nominally significant associations between arsenic exposure and the relative abundances of several bacterial taxa in the phylum Tenericutes, Proteobacteria, and Firmicutes . However, none of the associations retained significance after correction for multiple comparisons with FDR ≤ 5%. The relative abundances of the family Aeromonadaceae and genus Citrobacter were significantly associated with carotid IMT after adjustment for multiple comparisons with FDR ≤ 5%. There was a significant interaction between Citrobacter and time-weighted water arsenic in IMT ( P -value = 0.04). The data suggest that the gut microbiome may play an important role in the development of atherosclerosis, especially among individuals with higher levels of arsenic exposure.